Mediatization of Politics as an Element of Noopolitics - Borisovich Nikonov, Sergey; Sergeevich Labush, Nikolai; Stepanovich Puiy, Anatoli; Savova Georgieva, Elena; Sergeevich Lukin, Stanislav (International Journal of Engineering and Technology, 2018)
The work deals with the study of information strategy, namely noopolitics. In the course of the work, it has been revealed that one of the elements of the information strategy formation is the need to mediatize political processes. The understanding of political processes mediatization is considered in the part devoted to the scientific research outcomes. The work also considers a phenomenon such as rumours. This is not fake news, which is so often mentioned by politicians, but political reality, which is also an element of noopolitics. The main part of the work deals with the results of the implementation of the noopolitics when preparing and carrying out presidential elections in 2018, and the role of foreign states and politicians in strengthening power in Russia.